There is no such thing as Society. „Ferdydurke” w neoliberalizmie, postmodernizm i płeć - Majewska, Ewa (Przestrzenie Teorii, 2013)
In this article Ferdydurke is discussed as a forerunner of the logic of late capitalism with all its repercussions, as identified by Frederick Jameson. Gombrowicz’s novel is seen as an early prognosis of neoliberal ideology, with its demands for effectivity and productivity as well as negation of social and affective bonds. Margaret Thatcher’s aphorism: “there is no such thing as society” is a pretext for a critical analysis of Ferdydurke, including the feminist critics of the European vision of the subject built on fear of the Other. This feminist analysis of Ferdydurke reveals several problems with the notion of body – theories of Julia Kristeva (on abjection) and Lynda Nead (on the female nude) are employed to demonstrate this argument. The main conclusion that can be drawn from this analysis is that queer disruptions of the binary logic of gender oppositions do not necessarily produce anti-patriarchal results.